The Influence of The Relay Writing Method Assisted With Audio Visual Media on Procedure Text Writing Skills in Class VII Students at SMP Negeri 35 Palembang - ST. Fianda Kirana; Dessy Wardiah; Muhammad Ali (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to determine the effect of the relay writing method assisted by audio-visual media on procedural text writing skills in class VII students at Palembang Public Junior School 35.. This type of research is quantitative research that uses simple linear regression testing and multiple linear regression testing to answer the hypothesis in the research. The subjects in this research were class VII.3 as an experimental class with a total of 31 students and class VII.4 as a control class with a total of 33 students. Data collection techniques in this research used documentation and test techniques. Based on the results of testing the first hypothesis, it was found that there was an influence of the application of the relay writing method on the ability to write procedural texts which received a significant value of 0.000. The results of testing the second hypothesis show that there is an influence of the use of audio-visual media on the ability to write procedural texts which gets a significant value of 0.000. The results of testing the third hypothesis prove that there is an influence of applying the relay writing method with the help of the use of audio-visual media on procedural text writing skills which obtained a significant value of 0.000. Keywords : Estafet Writing, Audio Visual, Procedure Text.